Contributing factors to will adoption among urban Muslims community in Klang Valley / Nooriha Abdullah … [et al.] - Abdullah, Nooriha; Mohamad Basir, Faziatul Amillia; Mohd Ariffin, Azitadoly; Yusuff, Nur Diyana; Hidayah, Siti Nur (Universiti Teknologi MARA Selangor, 2017)
A will is a financial management instrument after one’s death. Majority of Muslims in Malaysia are aware and familiar with the term Islamic ‘will’. However, the number of Muslims who write a will is very low. Studies have concluded, the reluctance factors to write a will were due to a) lack of knowledge, b) religious factor and c) financial obligation. Therefore, it is the interest of the researchers to investigate the relationships of these three contributing factors towards will adoption among urban Muslim community in Klang Valley. The paper adopts a quantitative method of research design, which utilises descriptive analysis, correlation analysis and regression analysis to analyse the raw data. The results show all the independent variables have positive relationship with the dependent variable, in particular a strong significant relationship for knowledge. Thus, the paper suggests that any Muslims who are aware and has knowledge should write a will regardless of their age. In addition, writing a will before one’s death provides a peace of mind to that person.